Laryngeal vocal and endoscopic alterations after thyroidectomy under local anesthesia and hypnosedation - Souza,Lincoln Santos (2009)
Vocal alterations after thyroidectomy are generally related to laryngeal nerve injury or laryngotracheal mobility disorders caused by postoperative fibrosis or strap muscle lesion. AIM: this study aims to evaluate the frequency of vocal and rima glottidis disorders after thyroidectomy. MATERIALS AND METHOD: This is a prospective study based on 35 patients submitted to thyroidectomy under local anesthesia and hypnosedation. All patients underwent voice auditory perception evaluation, voice acoustic tests and videolaryngostroboscopy preoperatively, and at one week and at 30 days postoperatively. Bilateral cricothyroid muscle electromyography was performed on the thirtieth day after surgery to confirm the presence of injury in the external branch of the superior laryngeal nerve. RESULTS: 14.3% of the patients presented posterior glottis deviation before surgery and normal electromyography findings. Transient and permanent vocal alteration occurred in 25.7% and 14.2% of the patients respectively. CONCLUSION: voice disorders evaluated after voice auditory perceptive evaluation and voice acoustic tests were more intense in the group with superior laryngeal nerve external branch injury than in the injury-free dysphonic patient group. Oblique glottis can be present in normal patients; however its onset after thyroidectomy is indicative of superior laryngeal nerve external branch lesion.